Введение в творческий проект: учебное пособие - Ротарь О. В. Ольга Васильевна; Глухова М. В. Мария Владимировна; Искрижицкая А. В. Мария Владимировна; Ротарь В. Г. Виктор Григорьевич (Томск, Изд-во ТПУ, 2013)
Заглавие с титульного экрана